Engineering of Helicobacter pylori Dimeric Oxidoreductase DsbK (HP0231) - Bocian-Ostrzycka, Katarzyna M.; Grzeszczuk, Magdalena J.; Banaś, Anna M.; Jastrząb, Katarzyna; Pisarczyk, Karolina; Kolarzyk, Anna; Łasica, Anna M.; Collet, Jean-François; Jagusztyn-Krynicka, Elżbieta K. (Frontiers in Microbiology, 2016)
The formation of disulfide bonds that are catalyzed by proteins of the Dsb (disulfide bond) family is crucial for the correct folding of many extracytoplasmic proteins. Thus, this formation plays an essential, pivotal role in the assembly of many virulence factors. The Helicobacter pylori disulfide bond-forming system is uncomplicated compared to the best-characterized Escherichia coli Dsb pathways. It possesses only two extracytoplasmic Dsb proteins named HP0377 and HP0231. As previously shown, HP0377 is a reductase involved in the process of cytochrome c maturation. Additionally, it also possesses disulfide isomerase activity. HP0231 was the first periplasmic dimeric oxidoreductase involved in disulfide generation to be described. Although HP0231 function is critical for oxidative protein folding, its structure resembles that of dimeric EcDsbG, which does not confer this activity. However, the HP0231 catalytic motifs (CXXC and the so-called cis-Pro loop) are identical to that of monomeric EcDsbA. To understand the functioning of HP0231, we decided to study the relations between its sequence, structure and activity through an extensive analysis of various HP0231 point mutants, using in vivo and in vitro strategies. Our work shows the crucial role of the cis-Pro loop, as changing valine to threonine in this motif completely abolishes the protein function in vivo. Functioning of HP0231 is conditioned by the combination of CXXC and the cis-Pro loop, as replacing the HP0231 CXXC motif by the motif from EcDsbG or EcDsbC results in bifunctional protein, at least in E. coli. We also showed that the dimerization domain of HP0231 ensures contact with its substrates. Moreover, the activity of this oxidase is independent on the structure of the catalytic domain. Finally, we showed that HP0231 chaperone activity is independent of its redox function.